Malaysia Abridged SimSmoke Model - Towards Achieving 2025 and 2045 Smoking Prevalence Targets - Norashidah Mohamed Nor; Hana Ross; Wency Bui Kher Thinng; Judhiana Abdul Ghani; Norayana Hassan; Nizam Baharom (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
Volume:14 No.:3